1975
DOI: 10.1210/jcem-40-3-482
|View full text |Cite
|
Sign up to set email alerts
|

The Thyrotropin in Hydatidiform Moles is Human Chorionic Gonadotropin1

Abstract: Thyrotropic activity (TSH), measured by the McKenzie mouse bioassay, has been correlated with human chorionic gonadotropin (hCG) activity, measured by radioimmunoassay, in serum and tissue samples from 11 patients with hydatidiform mole and in partially and highly purified preparations of urinary hCG. Serum samples, taken at various times before and after removal of the moles, gave a ratio of 0.42 plus or minus 0.24 muU TSH/U hCG (mean plus or minus SD) (N)=43). In all cases where hCG activity fell below 150-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(51 citation statements)
references
References 0 publications
2
46
1
2
Order By: Relevance
“…These data would explain why overt hyperthyroidism is seen only in some women and then only in the first trimester, when hCG concentrations are greatest, and the occurrence of clinical and biochemical hyperthyroidism in women with hCG-producing tumours such as hydatidiform mole and choriocarcinoma (Miyai et al 1976). Indeed, the spectrum of increasing thyroid activity correlates with the severity of disease and the concentration of hCG, suggesting a causal relationship (Kenimer et al 1975). At the cellular level, hCG is believed to increase intracellular release of cAMP in the thyroid, which leads to a degranulation response, and the secretion of thyroxine.…”
Section: Discussionmentioning
confidence: 96%
“…These data would explain why overt hyperthyroidism is seen only in some women and then only in the first trimester, when hCG concentrations are greatest, and the occurrence of clinical and biochemical hyperthyroidism in women with hCG-producing tumours such as hydatidiform mole and choriocarcinoma (Miyai et al 1976). Indeed, the spectrum of increasing thyroid activity correlates with the severity of disease and the concentration of hCG, suggesting a causal relationship (Kenimer et al 1975). At the cellular level, hCG is believed to increase intracellular release of cAMP in the thyroid, which leads to a degranulation response, and the secretion of thyroxine.…”
Section: Discussionmentioning
confidence: 96%
“…The thyroid-stimulating activity of a commercial preparation of hCG was first demonstrated by Burger in a mouse bioassay (7). Subsequently, thyrotrophic activity has been found in several hCG preparations (4,5). These studies showed that hCG is the molar TSH and that 1 Unite hCG has intrinsic thyrotrophic activity equivalent to approximately 0.5 µU TSH in the Mouse bioassay (4).…”
Section: Solated Hypogonadotropic Hypogonadism (Ihh)mentioning
confidence: 98%
“…The beta subunit of hCG is unique to hCG but alpha-subunit is identical to that luteinizing hormone (LH), follicle stimulating hormone (FSH) and TSH (3). Human chorionic gonadotropin has thyroid-stimulating activity in bioassays in mice, rats, chicks and men (4)(5)(6). The thyroid-stimulating activity of a commercial preparation of hCG was first demonstrated by Burger in a mouse bioassay (7).…”
Section: Solated Hypogonadotropic Hypogonadism (Ihh)mentioning
confidence: 99%
“…hCG is synthesized primarily by syncytiotrophoblastic tissue, maintaining the corpus luteum and progesterone production in pregnancy (36,37). Receptors for the structurally similar glycoprotein hormones share significant homology in their extracellular binding domains, and hCG has confirmed thyroid-stimulating activity when present at high concentrations in serum because of a direct interaction of hCG with the TSH receptor (37)(38)(39)(40)(41)(42).…”
Section: Excess Tsh-like Materials and Gestational Trophoblastic Diseasesmentioning
confidence: 99%